The Streamlining of the Kabinakagami River Hydroelectric Project Environmental Assessment: What is the "Duty to Consult" with Other Impacted Aboriginal Communities When the Co-Proponent of the Project is an Aboriginal Community? - Holly L. Gardner (International Indigenous Policy Journal, 2015)
There is existing tension within many Aboriginal communities between economic development and preservation of traditional lands for the continued practice of traditional activities. The "duty to consult" doctrine has has become an important mechanism by which these concerns were identified and addressed (when possible) prior to development. This is a legal requirement that is rooted in the Constitution Act (1982) and subsequent legal case law that has further defined and outlined requirements under this obligation. This article describes the process that was carried out to advance the proposed Kabinakagami River Hydro Project Class Environmental Assessment in Northern Ontario, Canada with an emphasis on the approach to Aboriginal consultation. This project is unique because the co-proponent of the project is an Aboriginal community, with several neighbouring Aboriginal communities potentially affected by the project. This project raises questions about the approach to carrying out the duty to consult in an effective way. An evaluative framework was developed to examine timeline, information, means, and flexibility and transparency of the process to highlight shortcomings in the process and make recommendations for improvement.